Evolutionary tracks of chromosomal diversification in Trichopsis (Anabantiformes, Osphronemidae) fishes: New insights from a molecular cytogenetic perspective - BOONYADA MINGKWAN; FRANCISCO DE MENEZES CAVALCANTE SASSI; NAWARAT MUANGLENM; SITTHISAK PINMONGKHONKUL; KRIT PINTHONG; SAMPAN TONGNUNUI; PUN YEESIN; ALONGKLOD TANOMTONG; THOMAS LIEHR; MARCELO DE BELLO CIOFFI; WEERAYUTH SUPIWONG (Society for Indonesian Biodiversity, 2023)
Abstract. Mingkwan B, Sassi FDMC, Muanglenm N, Pinmongkhonkul S, Pinthong K, Tongnunui S, Yeesin P, Tanomtong A, Liehr T, Cioffi MDB, Supiwong W. 2023. Evolutionary tracks of chromosomal diversification in Trichopsis (Anabantiformes, Osphronemidae) fishes: New insights from a molecular cytogenetic perspective. Biodiversitas 24: 1551-1559. This study investigated the chromosomes of three Trichopsisspecies (namely Trichopsis pumila, Trichopsis vittata, and Trichopsis schalleri) using conventional (Giemsa stain, Ag-NOR) and molecularcytogenetic techniques. Fluorescence in situ hybridization (FISH) with repetitive DNAs, including 5S and 18S rDNAs, and microsatellites as probes were also performed. Our results indicated a conserved diploid number of 46 (2n) for all analyzed species of both sexes, although varying in their karyotype structure. Furthermore, T. schalleri and T. vittata karyotypes were presented with only acrocentric chromosomes (46a), while T. pumila had a submetacentric pair in addition to acrocentric ones (2sm+44a). Positive Ag-NOR sites were differentially found in each species adjacent to the acrocentric chromosome's centromeric and/or interstitial sub-centromeric regions. Both 5S and 18S rDNAs vary between the analyzed species, but all were localized in multiple sites. However, the distribution pattern of microsatellites differed in each species, mostly scattering at peri-centromeric and telomeric regions. These findings show that Trichopsis species, while having a conserved diploid number, differ significantly in the distribution of repetitive sequences in their karyotypes, particularly for rDNAs. These species-specific patterns can be useful for characterizing and identifying further different species and examining the evolutionary mechanisms that drove the evolution of these fishes' karyotypes.